Nitrate in drinking water and preterm birth: a national retrospective cohort study in New Zealand - Tim Chambers; Alice HM. Kim; Frank Dean; Isaac Bain; Jeroen Douwes; Mary Berry; Michael G. Baker; Simon Hales (Environmental Research, 2026)

Deep Dark Futures: Foresighting Human Impacts on Mesopelagic Ecosystem Services - Ben Scoulding; Alistair J. Hobday; Rowan Trebilco; Heidi Pethybridge; Ingrid van Putten; Katherine Baker; Karen Evans; David Green; Eriko Hoshino; Haris Kunnath; Clothilde Langlais; Tim P. Lynch; et al. (Fish and Fisheries, 2026)
Most of the global mesopelagic zone lies beyond the jurisdiction of any single government or entity, making equitable access and sustainable management for ecosystem services (ES) difficult. Here, a foresighting approach was used to examine the plausible consequences of four speculative scenarios of human activity on the mesopelagic zone and its associated ES. Large‐scale Harvest represented the provisioning ES, with concerns over unsustainable removal of mesopelagic biota. Climate Mitigation, a regulating ES, involved harvesting and then dumping mesopelagic biota to maximise carbon drawdown. In Geopolitical Manoeuvring, the scenario focused on cultural ES; mesopelagic fisheries were used as a geopolitical instrument to assert claims over ocean spaces. Finally, Mineral Extraction, a supporting ES, considered the impact of deep‐sea mining on mesopelagic ecosystems. Drivers and indicators for each scenario were identified, and qualitative network models were created to assess impact on the different system components using press perturbations. Model outputs highlighted the central role that mesopelagic biota play in supporting and regulating other ecosystem components and the likely negative impacts of reduced biomass on higher order predators and ocean carbon storage. Interestingly, biological indicators performed poorly as early warning signals of change across all scenarios; instead, the most effective indicators were related to science and technology, economics and governance. International agreements for sustainable use of the mesopelagic zone are needed to avoid loss of ES underpinning all scenarios. While this foresighting focused on the mesopelagic zone, the approach of developing scenarios, models and indicators has broader applicability to studies of other systems.

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Recognising and Protecting the National Benefit of Sustainable Fisheries in the UK - Sarah Coulthard; Ainsley Hatt; Phoebe Lewis; Bryce D. Stewart; Michael Roach; Robert Clark; Sam Fanshawe; Carole Sandrine White; Julie Urquhart; Jerry Percy; Tim Gray; Emily Bulled; et al. (Fish and Fisheries, 2025)
Sustainable commercial fishing makes valuable contributions to coastal regions and broader national benefits. This paper offers three arguments in relation to what is required for the societal benefits of sustainable fisheries to be fully realised and considers each in the context of the UK but with global relevance. First, there is a need to raise the profile of the full range of benefits that are delivered through sustainable fisheries to coastal communities and the broader public. In the UK, the delivery of a ‘national benefit’ objective through fisheries is now enshrined in law by the Fisheries Act, 2020; we operationalise this through a new framing that distils eight ‘national benefits’ that all sustainable fisheries should deliver. Second, better acknowledgement of what society gains from sustainable fisheries must be paralleled with recognition of what society is simultaneously at risk of losing through the decline of the fishing fleet. We detail this decline in a new analysis of long‐term UK data, which highlights that the decline is unequally felt, with some regions of the UK, and small‐scale fishing sectors, experiencing loss more acutely. This reality leads us to argue a third point, that if society is to retain and truly harness the benefits that flow from sustainable fisheries, governing bodies must act quickly to ensure that fisheries are environmentally sustainable, diverse and inclusive, pursuing fisheries that ‘leave no one behind’.

Examining campylobacteriosis disease notification rates: Association with water supply characteristics - Farnaz Pourzand; Alice H.M. Kim; Tim Chambers; Leah Grout; Michael G. Baker; Simon Hales (Environmental Research, 2025)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

The fish–mangrove link is context dependent: Tidal regime and reef proximity determine the ecological role of tropical mangroves - Michael Bradley; Alexia Dubuc; Camilla V. H. Piggott; Katie Sambrook; Andrew S. Hoey; Martial Depczynski; Tim J. Langlois; Monica Gagliano; Shaun K. Wilson; Katherine Cure; Thomas H. Holmes; Glenn I. Moore; et al. (Fish and Fisheries, 2024)
Tropical mangroves are known to support fish production, but natural variability in the link between mangrove habitats and fish populations undermines our ability to manage, conserve and restore this ecological relationship. This is largely due to undefined context‐dependence in the use of mangroves by fish. We collected a spatially extensive dataset of 494 mangrove fish assemblages using standardised Remote Underwater Video surveys of mangrove edge habitats from five environmentally heterogenous regions in the Indo‐Pacific. We used machine learning methods to define contextual limits of the use of mangroves by reportedly mangrove‐affiliated fish. We found that tidal range and proximity to coral reefs were the most important contextual predictors of the use of mangroves by most taxa. We established data‐driven threshold values for important contextual predictors of the use of mangroves by fish, offering new insights into the variable role played by tropical mangroves in supporting fish life histories. Where mangroves occur as part of reef seascapes in regions with limited tidal range (

Advancing botanical safety: A strategy for selecting, sourcing, and characterizing botanicals for developing toxicological tools - Suramya Waidyanatha; Bradley J. Collins; Tim Cristy; Michelle Embry; Stefan Gafner; Holly Johnson; Josh Kellogg; Julie Krzykwa; Siheng Li; Constance A. Mitchell; Esra Mutlu; Sarah Pickett; et al. (Food and Chemical Toxicology, 2024)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Temperature variability interacts with mean temperature to influence the predictability of microbial phenotypes - Fei‐Xue Fu; Bernhard Tschitschko; David A. Hutchins; Michaela E. Larsson; Kirralee G. Baker; Allison McInnes; Tim Kahlke; Arjun Verma; Shauna A. Murray; Martina A. Doblin (Global Change Biology, 2022)
Despite their relatively high thermal optima ( T opt ), tropical taxa may be particularly vulnerable to a rising baseline and increased temperature variation because they live in relatively stable temperatures closer to their T opt . We examined how microbial eukaryotes with differing thermal histories responded to temperature fluctuations of different amplitudes (0 control, ±2, ±4°C) around mean temperatures below or above their T opt . Cosmopolitan dinoflagellates were selected based on their distinct thermal traits and included two species of the same genus (tropical and temperate Coolia spp.), and two strains of the same species maintained at different temperatures for >500 generations (tropical Amphidinium massartii control temperature and high temperature, CT and HT, respectively). There was a universal decline in population growth rate under temperature fluctuations, but strains with narrower thermal niche breadth (temperate Coolia and HT) showed ~10% greater reduction in growth. At suboptimal mean temperatures, cells in the cool phase of the fluctuation stopped dividing, fixed less carbon (C) and had enlarged cell volumes that scaled positively with elemental C, N, and P and C:Chlorophyll‐ a . However, at a supra‐optimal mean temperature, fixed C was directed away from cell division and novel trait combinations developed, leading to greater phenotypic diversity. At the molecular level, heat‐shock proteins, and chaperones, in addition to transcripts involving genome rearrangements, were upregulated in CT and HT during the warm phase of the supra‐optimal fluctuation (30 ± 4°C), a stress response indicating protection. In contrast, the tropical Coolia species upregulated major energy pathways in the warm phase of its supra‐optimal fluctuation (25 ± 4°C), indicating a broadscale shift in metabolism. Our results demonstrate divergent effects between taxa and that temporal variability in environmental conditions interacts with changes in the thermal mean to mediate microbial responses to global change, with implications for biogeochemical cycling.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Forced summer stationary waves: the opposing effects of direct radiative forcing and sea surface warming - Hugh S. Baker; Tim Woollings; Cheikh Mbengue; Myles R. Allen; Christopher H. O’Reilly; Hideo Shiogama; Sarah Sparrow (Climate Dynamics, 2019)

Ship-Based Contributions to Global Ocean, Weather, and Climate Observing Systems - Shawn R. Smith; Gaël Alory; Axel Andersson; William Asher; Alex Baker; David I. Berry; Kyla Drushka; Darin Figurskey; Eric Freeman; Paul Holthus; Tim Jickells; Henry Kleta; et al. (Frontiers in Marine Science, 2019)

Species Matter: Wood Density Influences Tropical Forest Biomass at Multiple Scales - Oliver L. Phillips; Martin J. P. Sullivan; Tim R. Baker; Abel Monteagudo Mendoza; Percy Núñez Vargas; Rodolfo Vásquez (Surveys in Geophysics, 2019)

Ground Data are Essential for Biomass Remote Sensing Missions - Jérôme Chave; Stuart J. Davies; Oliver L. Phillips; Simon L. Lewis; Plinio Sist; Dmitry Schepaschenko; John Armston; Tim R. Baker; David Coomes; Mathias Disney; Laura Duncanson; Bruno Hérault; et al. (Surveys in Geophysics, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Aquatic food security: insights into challenges and solutions from an analysis of interactions between fisheries, aquaculture, food safety, human health, fish and human welfare, economy and environment - Simon Jennings; Grant D Stentiford; Ana M Leocadio; Keith R Jeffery; Julian D Metcalfe; Ioanna Katsiadaki; Neil A Auchterlonie; Stephen C Mangi; John K Pinnegar; Tim Ellis; Edmund J Peeler; Tiziana Luisetti; et al. (Fish and Fisheries, 2016)
Fisheries and aquaculture production, imports, exports and equitability of distribution determine the supply of aquatic food to people. Aquatic food security is achieved when a food supply is sufficient, safe, sustainable, shockproof and sound: sufficient, to meet needs and preferences of people; safe, to provide nutritional benefit while posing minimal health risks; sustainable, to provide food now and for future generations; shock‐proof, to provide resilience to shocks in production systems and supply chains; and sound, to meet legal and ethical standards for welfare of animals, people and environment. Here, we present an integrated assessment of these elements of the aquatic food system in the United Kingdom, a system linked to dynamic global networks of producers, processors and markets. Our assessment addresses sufficiency of supply from aquaculture, fisheries and trade; safety of supply given biological, chemical and radiation hazards; social, economic and environmental sustainability of production systems and supply chains; system resilience to social, economic and environmental shocks; welfare of fish, people and environment; and the authenticity of food. Conventionally, these aspects of the food system are not assessed collectively, so information supporting our assessment is widely dispersed. Our assessment reveals trade‐offs and challenges in the food system that are easily overlooked in sectoral analyses of fisheries, aquaculture, health, medicine, human and fish welfare, safety and environment. We highlight potential benefits of an integrated, systematic and ongoing process to assess security of the aquatic food system and to predict impacts of social, economic and environmental change on food supply and demand.

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Network analysis reveals that bacteria and fungi form modules that correlate independently with soil parameters - Alexandre B. de Menezes; Miranda T. Prendergast‐Miller; Alan E. Richardson; Peter Toscas; Mark Farrell; Lynne M. Macdonald; Geoff Baker; Tim Wark; Peter H. Thrall (Environmental Microbiology, 2015)
Summary Network and multivariate statistical analyses were performed to determine interactions between bacterial and fungal community terminal restriction length polymorphisms as well as soil properties in paired woodland and pasture sites. Canonical correspondence analysis ( CCA ) revealed that shifts in woodland community composition correlated with soil dissolved organic carbon, while changes in pasture community composition correlated with moisture, nitrogen and phosphorus. Weighted correlation network analysis detected two distinct microbial modules per land use. Bacterial and fungal ribotypes did not group separately, rather all modules comprised of both bacterial and fungal ribotypes. Woodland modules had a similar fungal : bacterial ribotype ratio, while in the pasture, one module was fungal dominated. There was no correspondence between pasture and woodland modules in their ribotype composition. The modules had different relationships to soil variables, and these contrasts were not detected without the use of network analysis. This study demonstrated that fungi and bacteria, components of the soil microbial communities usually treated as separate functional groups as in a CCA approach, were co‐correlated and formed distinct associations in these adjacent habitats. Understanding these distinct modular associations may shed more light on their niche space in the soil environment, and allow a more realistic description of soil microbial ecology and function.

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Fast demographic traits promote high diversification rates of Amazonian trees - Timothy R. Baker; R. Toby Pennington; Susana Magallon; Emanuel Gloor; William F. Laurance; Miguel Alexiades; Esteban Alvarez; Alejandro Araujo; Eric J. M. M. Arets; Gerardo Aymard; Atila Alves de Oliveira; Iêda Amaral; et al. (Ecology Letters, 2014)
The Amazon rain forest sustains the world's highest tree diversity, but it remains unclear why some clades of trees are hyperdiverse, whereas others are not. Using dated phylogenies, estimates of current species richness and trait and demographic data from a large network of forest plots, we show that fast demographic traits – short turnover times – are associated with high diversification rates across 51 clades of canopy trees. This relationship is robust to assuming that diversification rates are either constant or decline over time, and occurs in a wide range of Neotropical tree lineages. This finding reveals the crucial role of intrinsic, ecological variation among clades for understanding the origin of the remarkable diversity of Amazonian trees and forests.

Mammography utilization among Black and White Medicare beneficiaries in high breast cancer mortality US counties - Mandeep K. Virk-Baker; Michelle Y. Martin; Robert S. Levine; Xin Wang; Tim R. Nagy; Maria Pisu (Cancer Causes & Control, 2013)

Are compound leaves an adaptation to seasonal drought or to rapid growth? Evidence from the Amazon rain forest - Ana C. M. Malhado; Robert J. Whittaker; Yadvinder Malhi; Richard J. Ladle; Hans ter Steege; Oliver Phillips; L. E. O. C. Aragão; Timothy R. Baker; Luzmilla Arroyo; Samuel Almeida; Niro Higuchi; Tim J. Killeen; et al. (Global Ecology and Biogeography, 2010)
Aim To assess the hypotheses that compound leaves of trees in the Amazon forest are an adaptation to drought and/or rapid growth. Location Amazon rain forest, South America. Methods Genera from 137 permanent forest plots spread across Amazonia were classified into those with compound leaves and those with simple leaves. Metrics of compound leaf prevalence were then calculated for each plot and regression models that accounted for spatial autocorrelation were used to identify associations between climate variables and compound leaf structure. We also tested for associations between compound leaf structure and a variety of ecological variables related to life history and growth strategies, including wood density, annual increase in diameter and maximum height. Results One plant family, Fabaceae, accounts for 53% of compound‐leaved individuals in the dataset, and has a geographical distribution strongly centred on north‐east Amazonia. On exclusion of Fabaceae from the analysis we found no significant support for the seasonal drought hypothesis. However, we found evidence supporting the rapid growth hypothesis, with possession of compound leaves being associated with faster diameter growth rates and lower wood densities. Main conclusion This study provides evidence that possession of compound leaves constitutes one of a suite of traits and life‐history strategies that promote rapid growth in rain forest trees. Our findings highlight the importance of carefully considering the geographical distribution of dominant taxa and spatial clustering of data points when inferring ecological causation from environment–trait associations.

Toll-like receptor 7 is not necessary for retroviral neuropathogenesis but does contribute to virus-induced neuroinflammation - Stephanie D Lewis; Niranjan B Butchi; Mohammed Khaleduzzaman; Tim W Morgan; Min Du; Susan Pourciau; David G. Baker; Shizuo Akira; Karin E. Peterson (Journal of NeuroVirology, 2008)

Regional-scale Proterozoic IOCG-mineralized breccia systems: examples from the Wernecke Mountains, Yukon, Canada - Julie Hunt; Tim Baker; Derek Thorkelson (Mineralium Deposita, 2005)

Variation in potential for isoprene emissions among Neotropical forest sites - Peter Harley; Pérola Vasconcellos; Lee Vierling; Carlos Cleomir de S. Pinheiro; James Greenberg; Alex Guenther; Lee Klinger; Samuel Soares de Almeida; David Neill; Tim Baker; Oliver Phillips; Yadvinder Malhi (Global Change Biology, 2004)
As part of the Large Scale Biosphere–Atmosphere Experiment in Amazônia (LBA), we have developed a bottom‐up approach for estimating canopy‐scale fluxes of isoprene. Estimating isoprene fluxes for a given forest ecosystem requires knowledge of foliar biomass, segregated by species, and the isoprene emission characteristics of the individual tree species comprising the forest. In this study, approximately 38% of 125 tree species examined at six sites in the Brazilian Amazon emitted isoprene. Given logistical difficulties and extremely high species diversity, it was possible to screen only a small percentage of tree species, and we propose a protocol for estimating the emission capacity of unmeasured taxa using a taxonomic approach, in which we assign to an unmeasured genus a value based on the percentage of genera within its plant family which have been shown to emit isoprene. Combining this information with data obtained from 14 tree censuses at four Neotropical forest sites, we have estimated the percentage of isoprene‐emitting biomass at each site. The relative contribution of each genus of tree is estimated as the basal area of all trees of that genus divided by the total basal area of the plot. Using this technique, the percentage of isoprene‐emitting biomass varied from 20% to 42% (mean=31%; SD=8%). Responses of isoprene emission to varying light and temperature, measured on a sun‐adapted leaf of mango ( Mangifera indica L.), suggest that existing algorithms developed for temperate species are adequate for tropical species as well. Incorporating these algorithms, estimates of isoprene‐emitting biomass, isoprene emission capacity, and site foliar biomass into a canopy flux model, canopy‐scale fluxes of isoprene were predicted and compared with the above‐canopy fluxes measured at two sites. Our bottom‐up approach overestimates fluxes by about 50%, but variations in measured fluxes between the two sites are largely explained by observed variation in the amount of isoprene‐emitting biomass.

SKIN SWABBING FOR GENETIC ANALYSIS: APPLICATION TO DUSKY DOLPHINS ( LAGENORHYNCHUS OBSCURUS ) - April Dawn Harlin; Bernd Würsig; C. Scott Baker; Tim M. Markowitz (Marine Mammal Science, 1999)
A bstract Exfoliated skin was collected from bowriding dolphins with the use of a sterilized nylon scrub pad affixed to a wooden dowel. Initial tests of the effectiveness of the technique and dolphin behavioral responses were conducted on dusky dolphins off Kaikoura, New Zealand. During 14 sampling days, 128 contacts using this procedure were made with bowriding dolphins, of which 114 showed behavioral response. Responses during sampling were mild, with 11% of contacted individuals showing no visible response, and 66% of individuals which could be monitored for 30 sec after contact returning to bowride within 30 sec. Mean return time was 10 sec postcontact and did not vary significantly for groups of different sizes. Behavioral controls suggest that a proportion of responses could be explained by typical dolphin behavior in the presence of boats. Seventy‐eight percent of contacts resulted in successful collection of tissue samples. Sample time was three minutes on average. Size of group and behavioral state did not appear to influence sample time. Preliminary genetic analyses revealed that tissue collected by this technique was suitable for amplification and sequencing of mitochondrial DNA (mtDNA) via PCR. Comparisons of mtDNA control region sequences with those from known L. obscurus and other delphinid samples verified that this technique was robust against contamination from elements in sea water.